La nourriture des entités surnaturelles dans les croyances populaires néohelléniques - Stamatis Zochios (Cahiers Balkaniques)
In Modern Greek folk tales, men can obtain favour of some female supernatural figures, often called Kales Kuries, neraides or mires. To accommodate them, people had to prepare the table in a particular way, by displaying a certain type of food, different kinds of drinks and cutlery. If the women were satisfied with the offerings, they were rewarding the person with material or immaterial gifts.The aim of this article is to cast light on the ways in which people use food in order to get in contact with the supernatural, in Modern Greek popular beliefs about imaginary beings.